DEVELOPMENT OF FRUGAL WAVE SIMULATOR FOR COASTAL EROSION STUDY - Ana Sakura, Zainal Abidin; Hasmida, Hamza; Mohd Zulhatta, Kifli; Rasli, Muslimen; Mohd Danial, Ibrahim; Raudhah, Ahmadi; Mohd Shahrizal, Abdul Razak; May, Raksmey; Annisa, Jamali (Persatuan Saintis Muslim Malaysia (PERINTIS), 2022)
Wave energy has destructive potential. Coastal erosion study should cover bigger geographical area. However, cost of the equipment limits the coastal erosion study especially in the developed countries. Lab scale frugal wave simulator has been developed to assist coastal erosion study. The system consists of wave generator and buoy reader. The system is equipped with Adruino UNO R3 and sensors to measure wave amplitude, A and wave velocity, V. The developed system has been tested in 3.5m length of flume channel. The raw data of wave amplitude and wave velocity from the system were applied to get the wave energy attenuation and total sediment deposition rate. Similar numerical model of experimental flume channel has been developed and simulate in FLOW-3D HYDRO. The results from these two methods were compared and showed acceptable range of errors between 6.35% to 7.8%. The developed wave simulator will enable inclusive and equitable quality education opportunities for all.